Inside Taiwan's Sunflower Movement: Twenty-Four Days in a Student-Occupied Parliament, and the Future of the Region - Rowen, Ian (The Journal of Asian studies, 2015)
“Say goodbye to Taiwan,” wrote political scientist John Mearsheimer in a widely read article in the March-April 2014 issue of The National Interest. Threatened by China's rising economic might and abandoned by a weakening United States, one of Asia's most vibrant democracies was facing, in his “realist” analysis, an almost inevitable annexation via economic if not military force. “Time,” he wrote, “is running out for the little island coveted by its gigantic, growing neighbor.” But only days after publication, on March 18, activists and armchair analysts alike said hello to a new reality.